Effects of Check and Connect on Attendance, Behavior, and Academics: A Randomized Effectiveness Trial. (May 2014) - Maynard, Brandy R.; Kjellstrand, Elizabeth K.; Thompson, Aaron M.
Objectives: This study examined the effects of Check & Connect (C&C) on the attendance, behavior, and academic outcomes of at-risk youth in a field-based effectiveness trial. Method: A multisite randomized block design was used, wherein 260 primarily Hispanic (89%) and economically disadvantaged (74%) students were randomized to treatment or control conditions within 14 urban middle and high schools. The social service organization Communities In Schools implemented C&C in each of the schools, and the effects were compared to those of typical Communities In Schools services. Hierarchical linear modeling was used to account for the nested or random school-level effects when modeling student-level responses to the intervention. Results: Controlling for pretest performance and all relevant student- and school-level characteristics, C&C was significantly related to improvements in academic performance and reductions in disciplinary referrals. No significant effects were found for attendance. Conclusions: C&C is a promising intervention to improve outcomes for at-risk youth in school settings. Application to social work practice and research are discussed.